ANALISIS KUALITAS UDARA AMBIEN DENGAN PARAMETER PM2,5 DAN PM10 PADA AREA PABRIK PENGOLAHAN BIJIH NIKEL DI SULAWESI SELATAN - Sitorus, Isaghy Putri Utami; Irawan, Agus Bambang (Universitas Pembangunan Nasional Veteran Yogayakarta, 2024)
The mining activities of PT. XXX are conducted using the open cast mining method to extract nickel ore. In addition to mining, PT. XXX also processes its nickel ore. The nickel ore processing includes drying, reduction, smelting, refining, and granulation. These processing activities potentially cause particulate dispersion in the air. The purpose of this research is to determine air quality based on the Air Pollutant Standard Index (ISPU) using parameters of Particulate Matter 2.5 µm (PM2.5) and Particulate Matter 10 µm (PM10). This study employs a purposive sampling method for collecting ambient air quality samples using a portable Aeroqual S500 device. Measurements were taken at 5 points around the Process Plant area where air quality deterioration is likely to occur. The air quality data was analyzed based on the Indonesian Ministry of Environment and Forestry Regulation No. P.14/MENLHK/7/2020 concerning the Air Pollution Standard Index. Based on the measurement results at the five points in the PP area, several points exceeded the quality standards for Particulate Matter 2.5 µm (PM2.5) and Particulate Matter 10 µm (PM10). The highest concentrations of PM2.5 were found in the T1, measuring 30,666 µg/m3 and PM10 were found in the T3, measuring 105,031 µg/m3 respectively. However, according to the ISPU calculations performed at each sampling point, the air quality is still classified as moderate and remains acceptable for living organisms.. The mining activities of PT. XXX are conducted using the open cast mining method to extract nickel ore. In addition to mining, PT. XXX also processes its nickel ore. The nickel ore processing includes drying, reduction, smelting, refining, and granulation. These processing activities potentially cause particulate dispersion in the air. The purpose of this research is to determine air quality based on the Air Pollutant Standard Index (ISPU) using parameters of Particulate Matter 2.5 µm (PM2.5) and Particulate Matter 10 µm (PM10). This study employs a purposive sampling method for collecting ambient air quality samples using a portable Aeroqual S500 device. Measurements were taken at 5 points around the Process Plant area where air quality deterioration is likely to occur. The air quality data was analyzed based on the Indonesian Ministry of Environment and Forestry Regulation No. P.14/MENLHK/7/2020 concerning the Air Pollution Standard Index. Based on the measurement results at the five points in the PP area, several points exceeded the quality standards for Particulate Matter 2.5 µm (PM2.5) and Particulate Matter 10 µm (PM10). The highest concentrations of PM2.5 were found in the T1, measuring 30,666 µg/m3 and PM10 were found in the T3, measuring 105,031 µg/m3 respectively. However, according to the ISPU calculations performed at each sampling point, the air quality is still classified as moderate and remains acceptable for living organisms..